Investigation of changes in surface urban heat-island (SUHI) in day and night using multi-temporal MODIS sensor data products (Case Study: Tehran metropolitan) - Sirous Hashemi Darebadami; Ali Darvishi Boloorani; Seyed Kazem AlaviPanah; Mohammad maleki; Reza Bayat (تحقیقات کاربردی علوم جغرافیایی)
The term urban heat island (UHI), described the phenomenon of climate change in urban areas compared with surrounding rural areas. UHI effects include: increasing in energy and water consumption, air pollution expansion and interfering in thermal comfort. Surface urban heat island (SUHI) contains patterns of land surface temperature (LST) in urban areas that has interaction with UHI in urban canopy layer and urban boundary layer and investigate with thermal remote sensing. SUHI has diurnal and seasonal variations so requires multi-temporal data to analysis SUHI. In this study, the multi-temporal MODIS (Aqua and Terra) data product were used to analyze the SUHI in day and night in Tehran metropolitan. Physical and biophysical surface properties such as: land cover/land use (LULC), elevation, albedo, vegetation index (NDVI) and impervious surfaces index (NDBI) were used to interpretation of the LST and SUHI changes. The results showed that SUHI in Tehran, has spatial-temporal diurnal and seasonal variation. So that during warm days the surface urban cool island (SUCL) is formed in Tehran. At night times, SUHI index values was different between 2 and 5 ° C (maximum in the spring). The results also showed that different of land cover thermal properties, albedo and elevation was the most important factors is the diurnal changes of SUHI while phonological changes of vegetation and albedo, was the most important factors in seasonal changes of SUHI.